2016
DOI: 10.1186/s13062-016-0168-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the importance of cancer pathways by meta-analysis of differential protein expression networks in three different cancers

Abstract: BackgroundIt is believed that all cancers occur due to the mutation or change in one or more genes. In order to investigate the significance of the biological pathways which are interrupted by these genetic mutations, we pursue an integrated analysis using multiple cancer datasets released by the International Cancer Genome Consortium (ICGC). This dataset consists of expression profiles for genes/proteins of patients receiving treatment, for three types of cancer - Head and Neck Squamous Cell Carcinoma (HNSC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Associated genes were FGF2, FGFR2 and FGFR3. A recent study has suggested that PI3K and RAS signaling pathways are the two most important pathways in cancers of the head and neck, lung and kidney (72). In many cancers, PI3K pathway associated genes and proteins have been widely investigated as therapeutic targets (73).…”
Section: Identification Of Hcc Subtypes and Their Featuresmentioning
confidence: 99%
“…Associated genes were FGF2, FGFR2 and FGFR3. A recent study has suggested that PI3K and RAS signaling pathways are the two most important pathways in cancers of the head and neck, lung and kidney (72). In many cancers, PI3K pathway associated genes and proteins have been widely investigated as therapeutic targets (73).…”
Section: Identification Of Hcc Subtypes and Their Featuresmentioning
confidence: 99%
“…In particular, pathways such as NFkB, Trail, EGFR, PI3K, and TNF-α have been found to play signi cant roles in the high-risk group of ccRCC [5][6][7]. Targeting genes and proteins within the PI3K pathway has shown promise as a therapeutic approach for ccRCC, and the EGFR pathway is known to be crucial in the development of ccRCC and represents a potential therapeutic target [7]. Our research identi ed signi cant enrichments in GO and KEGG terms, including small molecule catalytic processes, apical parts of the cell, mesenchymal development, sarcomere, growth factor activity, and MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have highlighted the differences in various pathways across different ccRCC subtypes. In particular, pathways such as NFkB, Trail, EGFR, PI3K, and TNF-α have been found to play signi cant roles in the high-risk group of ccRCC [5][6][7]. Targeting genes and proteins within the PI3K pathway has shown promise as a therapeutic approach for ccRCC, and the EGFR pathway is known to be crucial in the development of ccRCC and represents a potential therapeutic target [7].…”
Section: Discussionmentioning
confidence: 99%
“…34 The Ras signaling pathway is rarely related to HNSCC, but this pathway had been shown to be highly significant to this cancer by a meta-analysis of differential protein expression networks. 35 In this pathway, eight informative genes were selected by the proposed method and all the genes (PIK3CA, PIK3C3, PIK3CG, PIK3CB, PIK3CD, HRAS, NRAS, KRAS) were found to be involved in HNSCC.…”
Section: Head and Neck Tumormentioning
confidence: 99%